Uses trends and error analysis in causal connectors in francophone, german and anglo-saxon learners of spanish (LE) - Ferreira, Anita; Elejalde, Jessica; Blanco, Lorena (Boletín de Filología, 2021)
The problem addressed in this article is related to the difficulties observed in the causal connectors in ELE learners of proficiency level A2 and B1 with French, German and English L1. To do this, a study is carried out in the areas of Corpus of Learners in computational format (Computer Learner Corporation, CLC) and Computer Aided Error Analysis. The variables considered correspond to the trend of use of causal connectors and the identification of causal errors according to the level of competence A2 and B1 and the mother tongue of the learners. From the CAELE corpus, a subcorpus of sentences with causal connectors has been delimited, made up of 1,578 textual sentences of Anglo-Saxon, French-speaking and German learners of ELE. The main objectives are to determine the frequencies of correct use and the frequencies of errors in the use of grounds. The results show a greater use of the causal connector because with 87% in both levels. The other causes follow with a percentage of 2% each: the causal connector as, the conjunctive phrases due to and since, the prepositive phrases thanks to that and because the conjunctive phrase since, the causal connector then and the phrase prepositive by + infinitive with 1%. The connector because it was searched with 3 different forms of writing: why; because. However, in terms of its functionality in all contexts of use, it turned out to express a causal relationship. Regarding the mother tongue, the German learners, unlike the other learners, were the ones who presented the greatestproblems in terms of the use of causal connectors.